Waterlogging and soil freezing during dormancy affected root and shoot phenology and growth of Scots pine saplings. (7th February 2019) - Roitto, Marja; Sutinen, Sirkka; Wang, Ai-fang; Domisch, Timo; Lehto, Tarja; Repo, Tapani
Abstract: Soil waterlogging is predicted to increase in the future climate in boreal regions due to increased precipitation. Snowmelt periods in winter may also become more common and further increase the amount of water in soil. It is not well known how waterlogging and soil freezing during winter affect the physiology, phenology and growth of trees. Our aim was to study the below- and aboveground responses of Scots pine ( Pinus sylvestris L.) saplings to waterlogging (WL) in frozen (Fr) and unfrozen (NoFr) soils in a growth chamber experiment. The soil was either −2 °C or +2 °C and either waterlogged or not in a split-plot design for 6 weeks during dormancy, with similar air conditions in all treatments, which were Fr + WL, NoFr + WL, Fr + NoWL and NoFr + NoWL. Needles showed a shift towards a deeper dormancy in frozen than unfrozen soil in terms of chlorophyll fluorescence ( F v / F m ), water potential and apoplastic electrical resistance. In spring, initiation of shoot elongation started earlier if the soil was frozen during dormancy. In Fr + WL, initiation of root growth was delayed by 20 days compared with other treatments; after that, the root growth peaked at the same time as needle elongation. Needles remained smaller in Fr + WL than in the other treatments, indicating that roots formed a strong sink for carbon. Shoot and root biomass were not negatively affected by waterlogging if the soil remained unfrozen. In Fr + WL, survival and growth capacity of new terminal and whorl buds, the number of bud scales and the number of dwarf shoots were reduced. We conclude that soil freezing on sites prone to waterlogging should be considered in management of boreal forests, especially in the face of predicted climate change.